Salt release from potato crisps - Tian, Xian; Fisk, Ian D. (Royal Society Of Chemistry, 2012)
The rate of salt release in-mouth from salted potato crisps was evaluated. It was hypothesised that a slow steady release of sodium would occur on chewing and hydration; to test this a crisp was chewed and held in the oral cavity without swallowing for 60 s. Sodium release was measured over the entire holding period, after 20–30 s a peak in salivary sodium levels was recorded. A similar trend was observed with sensory perceived saltiness by trained panellists. The results suggest that a significant proportion of the crisp’s salt flavouring is released in a pulse-type mechanism which would not be encountered when the crisp is exposed to normal eating patterns and would result in the consumption of a large proportion of unperceived sodium.